Magnetic properties of hexamethylbenzene - Fei Yen (Физика низких температур, 2019)
Magnetic susceptibility χ(T) measurements on hexamethylbenzene C₆(CH₃)₆ (HMB) as well as its deuterated analogue C₆(CD₃)₆ (HMB-d₁₈) in the range of 2–300 K are presented. When cooling, an uptick is detected in χ(T) when the external magnetic field is applied along the direction of the molecular planes which coincide with the onset of intra-molecular coupling of the CH₃ groups at T'C_H = 110.8 K for HMB and CD₃ groups at T'C_D = 126.7 K for HMB-d₁₈. Upon warming, the same discontinuities occur near TC_H = 117.8 K and TC_D = 132.2 K. Near 40 K, a peak anomaly is observed believed to be the system accessing its ground tunneling state. Near 20 K, the divergence of χ(T) suggests the establishment of long-range ordering, viz., inter-molecular gearing of the methyl group rotations. When the external magnetic field is applied perpendicular to the molecular planes, χ(T) is independent of temperature. Our findings reveal how correlated periodic motion of protons, a phenomenon inherent in many molecular solids, exhibits magnetic behavior that has been thus far overlooked.